“Alliud un “peius” nošķiršana atsavinājuma līgumos - Adamoviča, Patrīcija (Latvijas Universitāte, 2023)
Bakalaura darbs veltīts lietas ar trūkumiem (peius – latīņu val.) un citas lietas (aliud – latīņu val.) nošķiršanas problemātikai atsavinājuma līgumos. Bakalaura darbā pētīts jēdzienu “aliud” un “peius” saturs, civiltiesiskie aizsardzības līdzekļi, kā arī izvirzīti nošķiršanas kritēriji, balstoties uz Latvijas un ārvalsts tiesu praksi. Bakalaura darba ietvaros izveidota arī nošķiršanas shēma un tabula, norādot aliud un peius pazīmes un tiesiskos aizsardzības līdzekļus.

The bachelor thesis was devoted to the problem of differentiation of defective things (peius – latin) and other things (aliud – latin) in alienation contracts. The bachelor theses research the content of the concepts “aliud” and “peius”, their legal remedies, and sets the criteria of separation based on Latvian and foreign court practice. As a part of the bachelor’s thesis are a scheme and table of distinction between “aliud” and “peius”, indicating the features of aliud and peius and their legal remedies.
“Alliud and “peius” separation in alienation contracts
Keywords: Juridiskā zinātne; aliud; peius; defective thing; other thing